Ամերիկյան երազանքի գաղափարը Ս. Ֆիցջերալդի «Գիշերն անույշ է» վեպում - Շահմուրադյան, Անահիտ; Հարությունյան, Աննա (Զանգակ հրատ.)
Произведение «Ночь нежна» С. Фицджеральда является одной из самых мощных и глубоких его работ. Своего героя Дика автор представляет читателю талантливым, умным и полным духовного богатства, который, однако, духовно деградировал. Женившись на представительнице «очень богатого мира», Дик испытывает упадок духовного мира. Трагедия доктора личная и одновременно социальная. Это обвинение «очень богатым» и вердикт для буржуазной Америки, которая дала им власть и сделала их неприкосновенными. The novel “Tender Is the Night” is one of the most prominent works of F. Scott Fitzgerald. He described his hero Dick as a smart, talented and a person full of spiritual richness, but who was unable to prevent himself from moral degradation. Doctor’s tragedy is not only personal, but also social. The American son of a clergyman who is on the way to becoming a renowned psychologist when he falls in love with Nicole and marries her. Dick is extraordinarily charismatic and graceful at the start of the novel, but eventually falls to his ruin.
Keywords: Գրականագիտություն; Ամերիկյան գրականություն